The complete mitochondrial genome of Amur ide (Leuciscus waleckii waleckii). Issue 2 (3rd July 2019) - Zhang, Huanqing; Xu, Dajie; Shi, Lupeng; Dou, Huashan; Sha, Weilai
Abstract: In this study, the complete mitochondrial genome of Leuciscus waleckii waleckii was sequenced and got a whole length of 16605 bp. This genome was contain 2 rRNA, 22 tRNA, 13 protein-coding genes, 1 control region (D-loop) and 1 replication origin. And the nucleotide composition of this mitochondrial genome is 27.72% for A, 26.28% for T, 27.23% for C and 18.77% for G. To clarify the phylogenetic relationship of the Leuciscus waleckii waleckii, we concluded the phylogenetic tree using 12 PCGs (except ND6 ) of mitochondrial genome in Leuciscus waleckii waleckii and 16 other cyprinid fish by Bayesian inference (BI) methods and maximum-likelihood (ML). And the result show that Leuciscus waleckii waleckii was close to other Leuciscus species, especially Leuciscus baicalensis .